University Autonomy and Accountability in Russian Higher Education - Volkov, Andrei; Melnyk, Dara (International Higher Education, 2018)
Historically, the Russian State has had a tumultuous relationship with institutional independence. For the country to become again an academic superpower, it is necessary to expand university autonomy to enable independent strategic thinking on the leadership’s part and ensure that universities are accountable to their stakeholders. This article considers the broad issues of university autonomy and accountability in Russia from historical and contemporary perspectives.